MENINGKATKAN DAYA INGAT MELALUI METODE SENAM OTAK (BRAIN GYM) PADA ANAK USIA 5 – 6 TAHUN DI TK FATHRIZK KIDS PEKANBARU - Sri Suarni Sri Suarni; Daviq Chairilsyah Daviq Chairilsyah; Nurlita ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Brain gym is represent the simple movement corps which can be optimal of child growth. This method will activate two cleaving brain and combine the function of all brain shares to increase recall. The aim of this research is to know does any improvement for child recall by using this brain gym and the percentage of that improvement. For this research, the researcher used Research of Class Action method. That is this method uses 2 cycles and has 6 meeting. For the appliance of collecting the data was the research used a form of observation there are 23 of children. That were consisted of 14 boys and 9 girls. Based on the result of processing the data and observation of recall the children aged 5-6 year old. They got improvement in every cycles. Before brain gym method is used to increase recall at children was under standard that is 48,2%, while after the firs cycles of using this method it was increased to 61,5%, even in the second cycles it became 88,3%. So, it can be concluded that a brain gym improve a recall of children aged 5-6 year old especially in TK Fathrizk Kids Pekanbaru.Keywords: Brain Gym, Recall1